Preparation and properties of poly(vinyl alcohol)/chitosan blend bionanocomposites reinforced with cellulose nanocrystals/ZnO-Ag multifunctional nanosized filler - Azizi, Susan; Ahmad @ Ayob, Mansor; Hussein, Mohd Zobir; Ibrahim, Nor Azowa; Namvar, Farideh (Dove Medical Press, 2014)
A series of novel bionanocomposites were cast using different contents of zinc oxide-silver nanoparticles (ZnO-AgNPs) stabilized by cellulose nanocrystals (CNC) as multifunctional nanosized fillers in poly(vinyl alcohol)/chitosan (PVA/Cs) matrices. The morphological structure, mechanical properties, ultraviolet-visible absorption, and antimicrobial properties of the prepared films were investigated as a function of their CNC/ZnO-AgNP content and compared with PVA/chitosan/CNC bionanocomposite films. X-ray diffraction and field emission scanning electron microscopic analyses showed that the CNC/ZnO-AgNPs were homogeneously dispersed in the PVA/Cs matrix and the crystallinity increased with increasing nanosized filler content. Compared with pure PVA/Cs, the tensile strength and modulus in the films increased from 0.055 to 0.205 GPa and from 0.395 to 1.20 GPa, respectively. Ultraviolet and visible light can be efficiently absorbed by incorporating ZnO-AgNPs into a PVA/Cs matrix, suggesting that these bionanocomposite films show good visibility and ultraviolet-shielding effects. The bionanocomposite films had excellent antimicrobial properties, killing both Gram-negative Salmonella choleraesuis and Gram-positive Staphylococcus aureus. The enhanced physical properties achieved by incorporating CNC/ZnO-AgNPs could be beneficial in various applications.